(untitled) (Romanitas - Revista de Estudos Grecolatinos, 2017)
In this article, we propose to analyze the connection between Zeus Dodonaios and Serapis in the Greek world from the analysis of some magical gems bearing representations of Zeus Dodonaios enthroned as Sarapis and reports collected from the Greek Magical Papyri.